Optimal harvest age considering multiple carbon pools - a comment - Bjart Holtsmark; Michael Hoel; Katinka Holtsmark (Statistics Norway, Research Department, 2012)
In two recent papers, Asante and Armstrong (2012) and Asante et al. (2011) considered the question of optimal harvest ages. They found that the larger are the initial pools of dead organic matter (DOM) and wood products, the shorter is the optimal rotation period. In this note, it is found that this conclusion follows from the fact that the authors ignored all release of carbon from decomposition of DOM and wood products after the time of the first harvest. When this is corrected for, the sizes of the initial stocks of DOM and wood products do not influence the optimal rotation period. Moreover, in contrast to the conclusions in the two mentioned papers, our numerical analysis indicates that inclusion of DOM in the model leads to longer, not shorter, rotation periods.
Keywords: Q23; Q54; Q42; 330; Dead organic matter; forestry; Faustmann; carbon